Is consumption-Laffer curve hump-shaped? The VAT evasion channel - Aleksandar Vasilev (Journal of Economics Studies, 2018)
This paper shows a standard RBC model, when augmented with a VAT evasion channel, where evasion depends on the consumption tax rate, can produce a hump-shaped consumption La ffer curve. Furthermore, when the evasion channel is turned off , the hump in the Laff er curve disappears, resulting in a monotone relationship between the VAT rate and both the consumption and total tax revenue. This result comes in stark contrast to Hiraga and Nutahara (2017), who generate a peaking curve for consumption tax revenue in a model with a separable utility in consumption and leisure and no evasion. Their results are contingent on implausible values for elasticity parameters, and in addition predict a revenue-maximizing consumption tax rate which is implausibly high. The paper contributes to the public fi nance literature by providing evidence for the importance of the evasion mechanism, while at the same time adding to the debate about the existence of a peak tax rate for consumption tax revenue.
Keywords: D58; H26; 330; consumption tax; VAT evasion; consumption-Laffer curve; general equilibrium; fiscal policy; Bulgaria